1977
DOI: 10.1590/1809-43921977073417
|View full text |Cite
|
Sign up to set email alerts
|

Inpaichthys kerri n. g. n. sp., um novo peixe caracídeo do alto rio Aripuanã, Mato Grosso, Brasil

Abstract: lnpaichthys kerri n. g. n. sp., um novo peixe caracídeo do alto no Aripuanã, Mato Grosso, Brasil Resumo ~ descrito um novo peixe caracídeo (Pic;ces, Cypriniformes, Characoidei) pertencente a um novo g~nero Inpaichthys kerri n. g . n sp ., coletado p~rto da Estação do Núcleo Aripuanã do Instituto Nacbnal de Pesquisas da Amazônia (INPA), ao Norte de Mato Grosso, Brasil . A espécie nova possui linha lateral incompleta e nadadeira caudal nua. Os dentes são tricuspidados, em duas séries muito irregulares no pré-max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The genera Rachoviscus and Leptagoniates were provisionally placed in the subfamily following previous reports published in the literature (e.g. Géry, 1977;Géry and Junk, 1977). Three synapomorphies supported the monophyly of Aphyocharacinae: (1) presence of synchondral articulation between lateral ethmoid and anterodorsal border of orbitosphenoid; (2) fourth infraorbital absent or much reduced and bordered posteriorly by third and fifth infraorbitals; and (3) six or less branched pelvic-fin rays (Mirande, 2010).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The genera Rachoviscus and Leptagoniates were provisionally placed in the subfamily following previous reports published in the literature (e.g. Géry, 1977;Géry and Junk, 1977). Three synapomorphies supported the monophyly of Aphyocharacinae: (1) presence of synchondral articulation between lateral ethmoid and anterodorsal border of orbitosphenoid; (2) fourth infraorbital absent or much reduced and bordered posteriorly by third and fifth infraorbitals; and (3) six or less branched pelvic-fin rays (Mirande, 2010).…”
Section: Introductionmentioning
confidence: 68%
“…As reported by Mirande (2010), Rachoviscus was provisionally included within Aphyocharacinae based on general similarity between R. crassiceps and Inpaichthys kerri in overall body shape, coloration and, as previously noted by Géry and Junk (1977), the presence of non-aligned premaxillary teeth. This latter trait, in particular, is notable as it is also present in Hollandichthys multifasciatus, and may therefore represent evidence for close Mirande (2010) also suggested that Inpaichthys be included within Aphyocharacinae based on three morphological synapomorphies.…”
Section: Monophyly Of Aphyocharacinae (Sensu Mirande 2010)mentioning
confidence: 83%
See 1 more Smart Citation
“…The first of these characters is coded as polymorphic for P. alburnus, considering possible intraspecific variations. A variable presence of one or two premaxillary tooth rows was mentioned in the description of Inpaichthys kerri (Géry & Junk, 1977). In the observed specimens all the premaxillary teeth have extraosseous development and would be homologous to the teeth from the inner row of other species.…”
Section: Generalitiesmentioning
confidence: 78%
“…At that time it was quite noticeable that the fish fauna above the waterfalls was distinct from the fauna below, indicating that the falls act as an effective barrier to the movement of fishes in both directions. On the basis of material collected above the falls several new fishes were described, including Inpaichthys kerri, a new species and genus of Characidae proposed by Géry & Junk (1977).…”
Section: Introductionmentioning
confidence: 99%